Managing sustainable transport in Universiti Utara Malaysia, Sintok - Foong, Li June; Muhammad Haziq, Ismail; Ruth, Rabiam Deng; Aziz, Zulkufli (2015)
The increasing number and usage of private vehicles than public transport is impacting the environment sustainability including emissions that contribute to global warming, local air pollution and health problem. Besides, lack of efficient infrastructure and road safety in campus cause illegal parking that blocking the road path and indirectly may lead to congestion and minor accident. Therefore, it is important to persuade car users to choose more environmental friendly transportation. The objective of the present work is to identify the factors influencing the mode of choice among students based on gender and to determine mode of choice among student in campus.The methodological approach survey was conducted among 400 respondent of University Utara Malaysia. The research instrument use was questionnaire and measure using 5-point Likert scale.The aim of this study is to provide better understanding towards individual‟s mode of choice and characteristics influencing the mode choice of individuals. This paper can be used as a platform for future research in the area of sustainability in transportation such as developing more awareness among students‟ universities in Malaysia.